ANALISIS SOCIAL MEDIA INFLUENCER DAN E-WOM TERHADAP MINAT BELI FASHION PADA KONSUMEN GENERASI Z DI DKI JAKARTA - Shavira Nida Azzahra, (2021)
This research is a quantitive study conducted by researcher with the aim of knowing the influence of social media influencers and electronic word of mouth on purchase intention. This research was conducted by using a sample of 100 respondents from the population of DKI Jakarta who are Generation Z with an age range of 9-26 years and have an interest in buying fashion products through social media. The sampling method used was non-probability sampling using purposive sampling method. Data collection was carried out in this study using an online questionnaire via a google form which was distributed through the Whatsapp, Line, Twitter and Instagram applications. This research uses PLS (Partial Least Square) Analysis Technique with SmartPLS 3.0 application. The results obtained from this study are: (1) The Social Media Influencer variable has a negative and insignificant effect on purchase intention with a path coefficient value of -0.064. (2) The Electronic Word Of Mouth variable has a positive and significant effect on purchase intention with a path coefficient value of 0.761.